Overview Depression Levels for Ukrida Medical Faculty Students - Widjaya, Hartanto; Suryana, Melda; Ardi, Dharmawan; Sihombing, Riama (Jurnal MedScientiae, 2022)
Depression is a fundamental disorder in the group of mood disorders with or without accompanyinganxieties. The Faculty of Medicine is considered to have great demands and pressures in carrying outthe process, it can cause anxiety in students which, if it continues, can lead to depression. Thisresearch used a descriptive cross sectional study design. The research subjects were all students whowere according to the research criteria. The total sample obtained is 112 samples. The most agegroup in 18-22 years as many as 83 people (74.1%), the most common sex in women was 75 people(67.0%), the most common group living in boarding houses was 84 people (75.0%), the most frequenteconomic status who received monthly allowances of Rp. 500,000-5,000.00 was 97 people (86.6%),the GPA group above 3.00 as many as 92 people (82.1%), there is 49 people with a history of disease(43.8%), 111 non-smokers (99.1%), 95 people (84.8%) never drank alcohol. These group experiencednormal until severe levels of depression symptoms.